Causal impact of elevated body mass index on diabetic kidney disease: an integrated Mendelian randomization and Global Burden of Disease Study 2021 analysis - Ye-xin Chen; Dong-sen Hu; Mao-xuan Lin; Zi-heng Gao; Han-zhang Hong; Yu-xin Hu; Ling-zi Yao; Gai-wen Cui; Lin Wang (Renal Failure)
Background Elevated body mass index (BMI) has been implicated in the pathogenesis of diabetic kidney disease among patients with type 2 diabetes mellitus (T2DKD). However, establishing a causal relationship and quantifying the resultant global health impact remain challenging.Methods A two-sample Mendelian randomization (MR) analysis was conducted using summary-level data obtained from the IEU database. Multiple MR approaches, including inverse variance weighted (IVW), MR-Egger regression, weighted median, weighted mode, and simple mode methods, were implemented to ensure robust causal inference. In parallel, Global Burden of Disease Study (GBD) 2021 were analyzed to determine the trends in mortality and disability-adjusted life years (DALYs) in T2DKD attributable to high BMI (HBMI-T2DKD) from 1990 to 2021. Joinpoint regression was used to estimate the average annual percent change (AAPC). Bayesian age-period-cohort (BAPC) models were then applied to project the disease burden through 2049.Results MR analyses provided strong evidence for a causal relationship between elevated BMI and T2DKD. The GBD analysis revealed a sustained global increase in HBMI-T2DKD burden over the past three decades. Between 1990 and 2021, the result of AAPC indicated a persistent upward trend. The burden was particularly high among older adults, with the highest impact observed in East Asia and middle Socio-Demographic Index (SDI) region. By 2049, HBMI-T2DKD-related disease burden were projected to continue rising.Conclusions Elevated BMI is a significant causal risk factor for T2DKD. The integration of MR and GBD 2021 data underscores the urgent need for targeted public health interventions to reduce BMI levels, especially in high-risk regions and aging populations.